Assessment of Intramuscular Verapamil as Pharmacological Countermeasure in a Rat Model of Organophosphate DFP-induced Status Epilepticus - Yam Nath Paudel; Robert E. Blair; Elisa Hawkins; Matthew S. Halquist; Melissa Morgan; Jason Funderburk; Daniel Calvano; Jennifer Koblinski; Hope Richard; Laxmikant S. Deshpande (Neurotoxicity Research, 2025)
Lethal organophosphate (OP) exposure leads to status epilepticus (SE), which, despite standard-of-care (SOC) therapy, is associated with acute mortality and long-term morbidities. Neuronal injury and inflammation are reported following OP-SE, and drugs targeted at these processes have produced beneficial outcomes. Verapamil (VPM) is a calcium-channel blocker used as an antihypertensive drug and has been shown to exhibit neuroprotective and anti-inflammatory actions in experimental models of CNS injuries. Here, we investigated the feasibility of an adjunctive intramuscular (i.m.) VPM therapy in OP Diisopropyl Fluorophosphate (DFP)-induced SE. We also investigated the safety and toxicity of i.m. VPM and compared its pharmacokinetic (PK) profile to oral (p.o.) administration. Rats were injected with DFP (4 mg/kg, s.c.). One minute later, SOC treatment consisting of atropine (0.5 mg/kg, i.m.) and pralidoxime chloride (2-PAM; 25 mg/kg, i.m.) were administered, and at 1-hour post-SE, midazolam (1.78 mg/kg, i.m.) was given. Rats that met the behavioral SE severity criteria (Racine 4–5) were randomized into two treatment groups: those receiving saline (SAL) or VPM (10 mg/kg, i.m. bid , 3 days). Histological analysis was conducted to assess neuronal injury and injection-site pathology. In a separate group of rats, PK studies were conducted on blood and brain homogenates treated once with saline or VPM (10 mg/kg, p.o. or i.m.). Our data demonstrated that following DFP-SE, i.m. VPM achieved higher blood and brain levels and exhibited a favorable PK profile compared to p.o. route. VPM therapy did not cause significant muscle pathology and produced a robust neuroprotective response. Neuroinflammatory markers and long-term behavioral outcomes were not included in this study. Our studies provide evidence that the i.m. route is an effective method for delivering VPM following SE, producing significant neuroprotective outcomes compared to treatment with the standard-of-care alone in OP-SE.